SALT TOXICOSIS IN POULTS - A CLINICAL REPORT - K. Shoba; A. Srithar; N.D.J. Chandran (Journal of Veterinary and Animal Sciences, 2014)
Sodium (Na+) is the toxic ion in salt toxicosis of domestic fowls. Sodium chloride (common salt) is generally thought of as providing the majority of Na+ found in the diet. However, other sources of sodium such as sodium bicarbonate, can also contribute to the development of salt toxicosis. Elevated dietary sodium and increased concentrations of sodium chloride in the water increases water consumption, urine excretion and faecal moisture content in chicken (Martindale, 1975; Hijikuro, 1976). Growing birds are generally considered more susceptible to salt toxicosis because of the nature of renal development and physiology (Martindale, 1975; Hijikuro, 1976; Swayne et al., 1986 and Domingo et al., 1993). Experimental feeding of salt from 1.9 to 10 per cent to poults below two weeks of age resulted in ascites and increased mortality. However feeding of salts from 0.7 to 2 per cent did not produce mortality (Morrison et al., 1975; Pang et al., 1980). Ascites and ventricular failure (round heart) have been described both in chicken and turkeys with elevated NaCI levels in feed and water (Swayne et al., 1986).